Exploring the use of HPFRC and GFRP grids for the production of manhole covers - Oña, Mónica (2015)
Corrosion of the steel reinforced concrete elements is one of the common pathologies that limits the long-term performance of urban infrastructures. This problem causes the loss of structural serviceability by decreasing the concrete-steel bond strength and reducing the cross section of the reinforcements. The present study introduces a new system for developing free-corrosion resistance prefabricated manhole covers for applications in the aggressive environments, i.e. wastewater collector systems, sewer systems, stormwater systems, etc. Fibre reinforced cement composites were applied in this system in order to suppress the corrodible steel mesh and maintain the structural ductility as well. Application of fibre reinforced polymer (FRP) system is adopted as the additional solution for increasing the load carrying capacity of these elements without concerns about corrosion. The effectiveness of the applied strategy in developing the manhole covers in terms of load carrying capacity and failure mode is evaluated in this research. Furthermore, this paper discusses a FEM-based simulation, aiming to address the possibility of calibrating the constitutive model parameters related to fracture modes I and II.